Hadith #21 - Sahih Muslim - Shaqiq bin Salama (Sahih Muslim)
(The superstructure of) al-Islam is raised on five (pillars), testifying (the fact) that there is no god but Allah, that Muhammad is His bondsman and messenger, and the establishment of prayer, payment of Zakat, Pilgrimage to the House (Ka’ba) and the fast of Ramadan.
Grade: Sahih

Hadith #722 - Sahih Muslim - Shaqiq bin Salama (Sahih Muslim)
I was sitting in the company of Abdullah and Abu Musa when Abu Musa said: 0 ‘Abd al-Rahman (kunya of ‘Abdullah b. Mas’ud), what would you like a man to do about the prayer if he experiences a seminal emission or has sexual intercourse but does not find water for a month? ‘Abdullah said: He should not perform tayammum even if he does not find water for a month. ‘Abdullah said: Then what about the verse in Sura Ma’ida:” If you do not find water, betake yourself to clean dust”? ‘A
Grade: Sahih

Hadith #1804 - Sahih Muslim - Shaqiq bin Salama (Sahih Muslim)
A person from Banu Bajila who was called Nabik b. Sinan came to Abdullah and said: I recite mufassal surahs in one rak’ah. Upon this ‘Abdullah said: (You recite) like the recitation of poetry. I know the manner in which the Messenger of Allah (ﷺ) recited two surahs in one rak’ah.
Grade: Sahih

Hadith #4503 - Sahih Muslim - Shaqiq bin Salama (Sahih Muslim)
I heard Sahl b. Hunaif say at Siffin: O ye people, find fault with your (own) discretion. By Allah, on the Day of Abu Jandal (i. e. the day of Hudaibiya), I thought to myself that, if I could, I would reverse the order of the Messenger of Allah (ﷺ) (the terms of the truce being unpalatable). By Allah, we have never hung our swords on our shoulders in any situation whatsoever except when they made easy for us to realise the goal envisaged by us, but this battle of yours (seems to be an exceptio
Grade: Sahih

Hadith #6950 - Sahih Muslim - Shaqiq bin Salama (Sahih Muslim)
We were sitting at the door of Abdullah (b. Mas’ud) waiting for him (to come out and deliver a sermon to us). It was at this time that there happened to pass by us Yazid b. Mu’awiya an-Nakha’i. We said: Inform him (‘Abdullah b. Mas’ud) of our presence here. He went in and Abdullah b. Mas’ud lost no time in coming out to us and said: I was informed of your presence here but nothing hindered me to come out to you but the fact that I did not like to bore you (by stuffing your minds with
Grade: Sahih

Hadith #6952 - Sahih Muslim - Shaqiq bin Salama (Sahih Muslim)
Abu ‘Abd al-Rahman, we love your talk and so we yearn (to listen to you) and earnestly desire that you should deliver us lecture every day. Thereupon he said: There is nothing to hinder me in giving you talk (every day) but the fact that you may be bored. Allah’s Messenger (ﷺ) did not deliver sermons on certain days (fearing that we might be bored).
Grade: Sahih

Hadith #7298 - Sahih Muslim - Shaqiq bin Salama (Sahih Muslim)
Why don’t you visit ‘Uthman and talk to him? Thereupon he said: Do you think that I have not talked to him but that I have made you hear? By Allah. I have talked to him (about things) concerning me and him and I did not like to divulge those things about which I had to take the initiative and I do not say to my ruler: “You are the best among people,” after I heard Allah’s Messenger (ﷺ) as saying: A man will be brought on the Day of Resurrection and thrown in Hell-Fire and his intesti
Grade: Sahih